TEACHER’S STRATEGIES IN TEACHING SPEAKING SKILL FOR ELEVENTH GRADE STUDENTS AT SMA BOPKRI 2 YOGYAKARTA - Devi Widyaningsih; Rr. Hasti Robiasih (JELLT (Journal of English Language and Language Teaching), 2018)
The objectives of this research are (1) to describe the strategies used by the English teacher of the eleventh grade students of SMA BOPKRI 2 Yogyakarta in teaching speaking and (2) to find out how the English teacher applies the strategies in teaching speaking. This research is descriptive qualitative in the form of a case study. The data were collected from observation and video recording of XI IPA 1, XII IPA 2, and XI Bahasa. The data were transcribed, identified, described, and analyzed by using theory of Shaun Killianof on strategies in teaching speaking. The results indicate that not all of the strategies in teaching speaking were applied by the English teacher. In XI IPA 1 and XI IPA 2, the teacher applied six strategies, while in XI Bahasa, the teacher only applied four strategies in teaching speaking. The teacher applied the strategies to help students become active during the learning process. The strategies could help the students become more active in the teaching and learning process, because the implementation of those strategies was sufficiently executed.Â